Ambivalent character of leave policies development in Croatia: between pronatalist and gender equality agenda - Dobrotic, I (Ministerio de Empleo y Seguridad Social, 2018)
The paper explores the development of childcare-related leave policies in Croatia, putting a specific focus on rationale behind the reforms, with the leave policies development being considered primary through a gender lens. Namely, depending on dominant ideas and norms in particular country and time, leave policy design may have various features, involving different gender and class-related assumptions. Their understanding is particularly important if one wants to understand the outcomes of particular leave policy design as well as to work to transform the gendered nature of leave policies. Croatia makes an interesting case to explore the interaction between different policy ideas and the gendered dimension of leave policy design. On the one hand it demonstrates a resistance of once established policies as changeable and incoherent ideas behind the leave policy-making failed to undermine directly once established leave scheme; however, on the other hand these ideas succeed in gradual introduction of new elements in leave policy design, which foresee specific gender arrangements along social lines. An intense development of leave policies in Croatia started after the Second World War, when Croatia formed a part of socialist Yugoslavia. Leave policies formed a lynchpin of policy package which aimed to expand women’s labour market supply, greatly needed in the context of extensive industrialisation. The state-led process of women’s emancipation thus brought a one-year, post-natal maternity leave aimed at employed women, paid at the level of previous salary – divided into maternity leave which could be used 28 (or 45) days before the birth and until the child turns six months of age, and additional maternity leave which may be used until the child turns one. The leave policy design was based on gendered assumptions and it supported solely working mothers, while the father’s role as a primary breadwinner was not questioned. It explicitly supported a parenting model within which it was expected from women to temporary withdraw from the labour market after the childbirth, deeply ingrained in present values and norms in Croatia. After the collapse of state socialism, Croatia inherited a one-year, post-natal maternity leave paid at the level of previous salary, and the basic elements of the leave scheme have shown a high resistance to new policy ideas coming from both national and international actors. However, few new policy elements become gradually integrated within this scheme, relying on ideas coming from various policy paradigms and eventually bringing in an inconsistent character of leave policy design. As shown in this paper, reform initiatives since 1990s relied on ideas and elements inherent to different policy paradigms, asking for different goals as well as the features of leave policy design. On the one hand, with the onset of transition, Croatia has experienced a shift in main paradigm driving the leave policy development, which brought in new policy goals and instruments. There was a clear shift from state-led promotion of dual-earner family model, which reposed on one-year maternity leave and for that time moderately developed early childhood education and care services, prefiguring in some respects the activation dimension of the social investment paradigm, towards the familialistic paradigm. Familialistic paradigm aimed to endorse pronatalist goals and traditional gender roles, assigning women a reproductive function as a primary one, and asked for leave policies which would allow them to withdraw from the labour market in order to contribute to «demographic renewal». After a failure of policy proposals, which aimed to directly undermine leave policies inherited from socialist period (e.g. introduction of compulsory three-year maternity leave and a paid profession of mother caregiver, followed by the withdrawal of nurseries), these demands eventually resulted in introduction of three-year maternity leave for parents of three or more children and in the case of multiple births as well as increased leave benefits. On the other hand, a domestic-driven pronatalist agenda which asked for familialistic reforms was occasionally confronted with ideas coming from international actors. First, international financial agencies demanded a liberal-residual welfare regime, asking for cuts also in the area of leave benefits which was implemented in 1990s and early 2000s. After that also the EU entered the policy arena with its ambiguous gender equality agenda, and demanded father’s quotas within the leave policy design, bringing in two-months fathers quotas in 2013. However, the quotas were enacted solely for dual-earner families and in the case of eight-months parental leave (former six-months additional maternity leave), which may be used in the case of the birth of the first and the second child, imposing different gender arrangements for different groups of parents. Croatia thus failed to formulate a coherent policy paradigm, which would drive a leave policy reforms, what resulted in often, ill- advised and uncoordinated reforms and brought an ambivalent amalgam of leave policy design. It combines both familialistic (e.g. comparatively long maternity leave, a three-year leave for some parents, parent-caregiver status in the City of Zagreb) and gender equality (eg two- months father’s quotas) oriented elements as well as pronatalist elements (e.g. longer leaves and cash-for-care scheme target families with more children), and run the risk to encourage women with more children and of lower socio- economic status to withdraw from the labour market. Leave policies remained highly instrumental and primary seen as a policy instrument, which may serve pronatalist agenda, and not a gender equality per se. Recent reforms and discussion, i.e. the reliance on elements of both familialistic and social investment paradigm in reform proposals and actual introduction of parent-caregiver status in the City of Zagreb, which started to be advocated as a solution appropriate especially for low- skilled mothers and low-earning families (also families living in depopulated areas), only strengthen this. It also strengthened an ambiguity of leave policy design, and pose a risk of further development of leave scheme inconsistent in its character, which tend to insist on different gender arrangements divided along social lines.